Integrated yoga therapy for teaching toothbrushing skills to children with autism spectrum disorder: A qualitative study of parents' perceptions - R Eswari; G S Prathima; A Sanguida; Meena Ramanathan; Ananda Balayogi Bhavanani; E Harikrishnan (Wolters Kluwer Medknow Publications, 2019)
Background: Children with autism spectrum disorder (ASD) exhibit poor oral health due to lack of manual dexterity. Regular training methods such as visual pedagogy and video modeling (VM) for developing the skill of toothbrushing do not address the core deficits which facilitate their effective and quick learning. Hence, there arises the need of an integrated therapy which can complement these regular training techniques. Aim: This study aimed to evaluate whether yoga can complement the regular training methods in teaching the brushing skill to children with ASD. Materials and Methods: Two groups of 36 children with ASD aged 7-15 years were imparted visual pedagogy and VM in Group I and additional yoga in Group II. Assessment of toothbrushing skill was done by parents and teachers independently using the perception and assessment forms, respectively. Results: By the end of 6 months, higher percentage of parents of children in Group II observed improvements in their child's brushing skill as compared to parents of children in Group I. Based on the teachers' observation, there was a statistically significant difference in the mean number of days the children watched the video completely (p = 0.001), with children in Group II watching the video for more number of days. Conclusion: Yoga has a positive and additive role along with the regular training methods for toothbrushing in children with ASD.